The Role of Islamic Religious Education Teachers in Overcoming Bullying at Junior High School - Putra, Safril Aditia; Nurhaliza, Indriyani; Arif, Saiful (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2024)
This study aims to identify the role of Islamic Religious Education (PAI) teachers in addressing bullying behavior at junior high schools in Pamekasan Regency. Using a qualitative descriptive approach, the study reveals that bullying arises from peer influence, seniority, and inadequate school supervision. The dominant form of bullying is verbal, including mocking and insults, leading to concentration issues, anxiety, and depression among victims. PAI teachers play a strategic role by teaching religious values, empathy, and tolerance. They also act as role models and mentors, collaborating with counselors, parents, and the school community to create an inclusive and bullying-free environment. The study recommends strengthening anti-bullying policies, character education programs, and strict supervision as effective measures to prevent and address bullying in schools.